Enhanced TC in SrRuO3/DyScO3(110) thin films with high residual resistivity ratio - Nathaniel J. Schreiber; Ludi Miao; Hari P. Nair; Jacob P. Ruf; Lopa Bhatt; Yorick A. Birkholzer; George N. Kotsonis; Lena F. Kourkoutis; Kyle M. Shen; Darrell G. Schlom (APL Materials, 2023)
Epitaxial untwinned SrRuO3 thin films were grown on (110)-oriented DyScO3 substrates by molecular-beam epitaxy. We report an exceptional sample with a residual resistivity ratio (RRR), ρ [300 K]/ρ [4 K] of 205 and a ferromagnetic Curie temperature, TC, of 168.3 K. We compare the properties of this sample to other SrRuO3 films grown on DyScO3(110) with RRRs ranging from 8.8 to 205, and also compare it to the best reported bulk single crystal of SrRuO3. We determine that SrRuO3 thin films grown on DyScO3(110) have an enhanced TC as long as the RRR of the thin film is above a minimum electrical quality threshold. This RRR threshold is about 20 for SrRuO3. Films with lower RRR exhibit TCs that are significantly depressed from the intrinsic strain-enhanced value.